Restrukturisasi Kognitif Untuk Mengurangi Gejala Insomnia: Cognitive Restructuring to Reduce Symptoms of Insomnia - Esty Aryani Safithry (Suluh: Jurnal Bimbingan dan Konseling, 2017)
Lack of sleep can cause mood disorders, emotions, concentration and cause laziness. Cognitive restructuring can be used to reduce symptoms of insomnia; this therapy is a form of psychological treatment that is based on cognitive theories. The research subjects were UM Palangkaraya students. This type of research is a case study. The results showed that this therapy could reduce the symptoms of insomnia, which was marked by changes in positive, negative thinking which eventually generated positive behaviours which could then help them to start sleeping and maintain their sleep quality.